METHOD OF CONSTRUCTING TRANSVERSE INFLUENCE LINES OF DISTRIBUTION COEFFICIENTS EFFORT BETWEEN BEAMS IN SPANS OF HIGHWAY BRIDGES ACCORDING TO THE STATIC TEST - Sukhorukov, B. D. (Science and Transport Progress, 2006)
The article proposes a method of constructing the transversal lines of distribution ratios influence for the span structures of road bridges, based on the results of just one application of tester loading.